Zapotrzebowanie na edukację z zakresu profilaktyki nowotworu jądra w grupie młodych mężczyzn - badania wstępne - Pietraszek, Agata; Brzozowska, Joanna; Charzyńska-Gula, Marianna; Łuczyk, Marta; Stanisławek, Andrzej; Łuczyk, Robert (Journal of Education, Health and Sport, 2015)
Pietraszek Agata, Brzozowska Joanna, Charzyńska-Gula Marianna, Łuczyk Marta, Stanisławek Andrzej, Łuczyk Robert. Zapotrzebowanie na edukację z zakresu profilaktyki nowotworu jądra w grupie młodych mężczyzn - badania wstępne = The need for education on testicular cancer prevention among young men - a preliminary report. Journal of Education, Health and Sport. 2015;5(7):521-532. ISSN 2391-8306. DOI 10.5281/zenodo.21758 http://dx.doi.org/10.5281/zenodo.21758 https://pbn.nauka.gov.pl/works/597083 POL-index https:/pbn.nauka.gov.pl/polindex/browse/article/article-4e7ded6e-f8c7-4d74-9378-5568a10e8349 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A521-532 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.06.2015. Revised 15.07.2015. Accepted: 25.07.2015. Zapotrzebowanie na edukację z zakresu profilaktyki nowotworu jądra w grupie młodych mężczyzn - badania wstępne The need for education on testicular cancer prevention among young men - a preliminary report Agata Pietraszek1, Joanna Brzozowska2, Marianna Charzyńska-Gula3, Marta Łuczyk1, Andrzej Stanisławek1, Robert Łuczyk4 1. Zakład Onkologii, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie, Polska 2. Zakład Etyki i Filozofii Człowieka, Wydział Nauk o Zdrowiu, Katedra Nauk Humanistycznych, Uniwersytet Medyczny w Lublinie, Polska 3. Wydział Nauk Społecznych i Humanistycznych, Państwowa Wyższa Szkoła Zawodowa im. prof. Stanisława Tarnowskiego w Tarnobrzegu, Polska 4. Katedra Interny z Zakładem Pielęgniarstwa Internistycznego, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie, Polska 1. Department of Oncology, Chair of Oncology and Environmental Health, Faculty of Health Science, Medical University of Lublin, Poland 2. Department of Ethic and Human Philosophy, Chair of Humanities, Faculty of Health Science, Medical University of Lublin, Poland 3. Faculty of Social Sciences and Humanities, Higher Vocational School Memorial of Prof. Stanislaw Tarnowski in Tarnobrzeg, Poland 4. Chair of internal Medicine and Department of Internal Medicine in Nursing, Faculty of Health Science, Medical University of Lublin, Poland Słowa kluczowe: nowotwory jąder, samobadanie, zachowania zdrowotne, zdrowie mężczyzny. Key words: Testicular Neoplasms, Self-Examination, Health-Behavior, Men’s Health. Adres do korespondencji: Agata Pietraszek, Katedra Onkologii I Środowiskowej Opieki Zdrowotnej, Uniwersytet Medyczny w Lublinie, ul. S. Staszica 4 (Collegium Maximum), Lublin 20-081, agata.pietraszek.umlub@gmail.com Streszczenie Wstęp. Rak jądra jest najczęściej występującym nowotworem wśród mężczyzn w wieku od 15 do 35 lat. Badania sugerują wysoki potencjał wykorzystania samobadania jąder w profilaktyce raka jąder. Niemniej jednak, wiele doniesień wskazuje na niską wiedzę oraz słabe rozpowszechnienie samobadania wśród młodych mężczyzn wielu narodowości. Cel pracy. Ocena zapotrzebowania na informacje dotyczące samobadania i chorób nowotworowych jąder w wybranej grupie młodych mężczyzn oraz znaczenia pracowników ochrony zdrowia, jako źródła tych informacji. Materiał i metody. Badania przeprowadzono metodą sondażu diagnostycznego z techniką ankiety. Narzędziem badawczym zastosowanym w pracy był autorski kwestionariusz ankiety. W badaniu wzięło udział 198 młodych mężczyzn w wieku od 17 do 29 lat Wyniki. Nawet 73,2% ankietowanych nigdy nie słyszało o samobadaniu jąder. Ponad 79,8% mężczyzn deklarowała, iż nie wykonuje samobadania. Głównym powodem nie wykonywania samobadania przez respondentów był brak wiedzy odnośnie techniki badania. Nawet 50,5% ankietowanych chciałoby wziąć udział w edukacji onkologicznej na temat samobadania jąder. Preferowaną formą edukacji onkologicznej wśród badanych mężczyzn była głownie łatwo dostępne ulotki i broszury (49,5%). Respondenci deklarowali, iż do praktykowania samobadania jąder mogłaby ich zmotywować głównie partnerka (49,2%). Wnioski. Rozpowszechnienie samobadania jąder wśród badanych mężczyzn jest bardzo niskie. Konieczne jest pilne opracowanie i wdrożenie sprawdzonych programów edukacyjnych skierowanych na profilaktykę nowotworów jąder. Summary Background. Testicular cancer is the most common type of neoplasm among men aged 15-35. The research suggests a high potential of testicular self-examination in testicular cancer prevention. However, numerous studies demonstrate a poor level of knowledge on and a low popularity of testicular self-examination among young men of various nationalities. Objectives. The assessment of the respondents' demand for information on self-examination and testicular cancer in the selected group of young men and of the role of medical professionals as an information source. Material and methods. The research was conducted with the use of the diagnostic survey method and the questionnaire technique. A questionnaire prepared by the authors constituted the research instrument for the study. The survey included 198 young men aged 17-29. Results. As many as 73.2% of the respondents had never heard of testicular self-examination. Over 79.8% of the men declared that they had not performed the self-examination. The major reason why the respondents did not practice the self-examination was the lack of knowledge on the technique. As many as 50,5% of the surveyed would like to participate in oncological education on testicular self-examination. The preferred forms of oncological education for the surveyed men were easily accessible leaflets and brochures (49.5%). The respondents claimed that they could be motivated to practice testicular self-examination by their partner (49.2%). Conclusions. Testicular self-examination was found to be rarely practiced by the surveyed men. Thus, there is an urgent need to develop and implement reliable educational programmes focussing on testicular cancer prevention.